High prevalence of antibiotic resistance in commensal Escherichia coli among children in rural Vietnam - Dyar Oliver; Hoa Nguyen; Trung Nguyen V; Phuc Ho D; Larsson Mattias; Chuc Nguyen TK; Lundborg Cecilia (BMC Infectious Diseases, 2012)
Abstract Background Commensal bacteria represent an important reservoir of antibiotic resistance genes. Few community-based studies of antibiotic resistance in commensal bacteria have been conducted in Southeast Asia. We investigated the prevalence of resistance in commensal Escherichia coli in preschool children in rural Vietnam, and factors associated with carriage of resistant bacteria. Methods We tested isolates of E. coli from faecal samples of 818 children aged 6-60 months living in FilaBavi, a demographic surveillance site near Hanoi. Daily antibiotic use data was collected for participating children for three weeks prior to sampling and analysed with socioeconomic and demographic characteristics extracted from FilaBavi's re-census survey 2007. Descriptive statistics were generated, and a logistic regression model was used to identify contributions of the examined factors. Results High prevalences of resistance were found to tetracycline (74%), co-trimoxazole (68%), ampicillin (65%), chloramphenicol (40%), and nalidixic acid (27%). Two isolates were resistant to ciprofloxacin. Sixty percent of isolates were resistant to three or more antibiotics. Recent sulphonamide use was associated with co-trimoxazole resistance [OR 3.2, 95% CI 1.8-5.7], and beta-lactam use with ampicillin resistance [OR 1.8, 95% CI 1.3-2.4]. Isolates from children aged 6-23 months were more likely to be resistant to ampicillin [OR 1.8, 95% CI 1.3-2.4] and co-trimoxazole [OR 1.5, 95% CI 1.1-2.0]. Associations were identified between geographical areas and tetracycline and ampicillin resistance. Conclusions We present high prevalence of carriage of commensal E. coli resistant to commonly used antibiotics. The identified associations with recent antibiotic use, age, and geographical location might contribute to our understanding of carriage of antibiotic resistant commensal bacteria.